VIOLATIONS OF CHILDREN’S RIGHTS IN SUDAN AND THEIR CIRCUMSTANCES: THE CURRENT SITUATION AND THE POSSIBILITY OF SOLUTIONS - KARAMALLA-GAIBALLA, NAGMELDIN (Society Register, 2021)
This paper aims to demonstrate the main aspects and weaknesses of children's rights in Sudan and describe how to work towards enhancing the immediate response to violations against children. This discussion will help develop future plans to strengthen the enforcement of children’s rights in Sudan and create an environment that protects children's rights against all kinds of violations. This paper presents the current situation of children’s rights violations in Sudan and factors that have a great and direct impact on these situations, especially social and cultural factors concerning female circumcision, genital mutilation, and marriage of underage girls; and laws that violate the dignity of Sudanese children, such as laws related to flogging, imprisonment, and death. The article also addresses issues of wars and internal conflicts and their impact on children, including their recruitment and trafficking. It also discusses the weaknesses of laws in place to protect children in Sudan and the changes these laws have undergone in recent years, especially the fundamental changes following the revolution that broke out in Sudan in 2018, which replaced the dictatorial military regime with Islamic orientations and trying to find objective solutions.